1975
DOI: 10.1159/000197690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatty Acids on the Stimulated Gastric Secretion in Man

Abstract: Solutions and emulsions of sodium or potassium salts in a series of saturated fatty acids from C8 to C18 were given in a dose of 0.5 g intraduodenally to healthy males or patients with healed duodenal ulcer. A double-lumen Sarles tube with a balloon placed in the proximal duodenum was used. The substances were instilled after a plateau of gastric acid secretion induced by a continuous infusion of pentagastrin was reached. In order to exclude unspecific effects, the test solutions were adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Differences in experimental design may explain this discrepancy: First, Kihl and Olbe [1,8] used a bolus injection of high amounts (5-40 ml) of pure oleic acid, and others used oleic acid at pH 8.0 [2], The pH and the concentration of oleic acid in the perfusates used in the present study are within the physiological range (that is postprandial [9]). Second, in contrast to other studies [1,2,8], we only perfused the duodenum with fat and avoid the jejunal component [10] in the inhibition of pentagastrin-induccd gastric acid secretion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Differences in experimental design may explain this discrepancy: First, Kihl and Olbe [1,8] used a bolus injection of high amounts (5-40 ml) of pure oleic acid, and others used oleic acid at pH 8.0 [2], The pH and the concentration of oleic acid in the perfusates used in the present study are within the physiological range (that is postprandial [9]). Second, in contrast to other studies [1,2,8], we only perfused the duodenum with fat and avoid the jejunal component [10] in the inhibition of pentagastrin-induccd gastric acid secretion.…”
Section: Discussionmentioning
confidence: 94%
“…The effect of oleyl alcohol was insignificant. It is concluded that the carboxyl group of the fat molecule has an important role in the inhibi tion of gastric acid secretion, and the effect could in part be attributable to the release of secretin into plasma.The presence of fat in the duodenum is known to inhibit gastric acid secretion [1], Oleic acid forms a considerable proportion of the dietary fat and seems to inhibit more than other fatty acids and triglycerides [2], The role of the lipo-and hydrophilic ends of the oleic acid molecule in the inhibition has never been evaluated.The aim of the present study was to clarify the importance of the terminal carboxyl group of the oleic acid molecule in the inhibition of pentagastrin-stimulated gastric acid secretion in man. …”
mentioning
confidence: 99%
“…The identity of enterogastrone remains unsettled. It has been proposed that more than one enterogastrone may be released by fat, depending upon the kind of fatty acid involved and the different receptors responsible for fat-induced inhibition of acid secretion [4]. G1P seems to be one of the prime candidates, but the evidence is not final.…”
Section: Discussionmentioning
confidence: 99%
“…by ingestion of foods containing fat or by the presence of fat in the duodenum [1][2][3][4]. Fat has been shown to inhibit acid secretion stimulated both by histamine and by exogenous gastrin [2][3][4][5]. The mechanism underlying this effect is unknown, but enterogastrone, a humoral factor released by fat, has been postulated as the agent responsible for these effects [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation